Chances and barriers of building information modelling in wastewater management. (16th March 2023) - Kretschmer, Florian; Franziskowski, S.; Huber, F.; Ertl, T.
Abstract: The advancing digitalisation is one of the great challenges of our times. Related activities also concern the wastewater sector. In the field of building construction, one emerging approach is building information modelling (BIM). The presented work investigates to which extent BIM practices have already found their way to wastewater management, and what kind of benefits and constraints are incorporated. Information is collected by means of a literature review and international expert surveys. Results indicate that several BIM-related key elements are already well established in the sector, but not necessarily in the intended manner. Consequently, the digital transition in the wastewater sector is not about replacing existing procedures and techniques but to rethink and optimise them. This primarily concerns data and information management in combination with the application of digital tools. Furthermore, wastewater management requires more integrated approaches, involving interdisciplinary/collaborative concepts and life cycle perspectives. Appropriate change management is necessary to give support and guidance to employees during the transition process. Furthermore, also from the political side, a clear definition and communication of the pursued digital vision is important. This article aims at stimulating discussion and research to optimise wastewater management from the digital perspective. HIGHLIGHTS: To cope with today's challenges in the (waste)water sector, digitalisation is considered a suitable tool. Building information modelling (BIM) can help to optimise existing working practices and procedures in various ways. This article presents and discusses the chances and barriers of BIM to support the digital transition in the wastewater sector.